PERAWATAN GIGI P1 ATAS DENGAN PERCABANGAN DI SALURAN AKAR SEPERTIGA APEKS (LAPORAN KASUS) - Anggraeni Anggraeni; Safrida Hoesin; Kamizar Kamizar (Faculty of Dentistry, Universitas Indonesia, 2015)
This case study reviewed conventional root canal treatment of a maxillary root canal treatment which unexpectedly had a single canal with two foramens. This tooth was recognized as the last frequent tooth appeared neither with additional canal nor unusual root anatomy. Retreatment for this case was successful through widening of the access cavity and the root canal. While trying the master cone, it revealed that the canal splitted and had two foraments. A thorough knowledge of the root canal anatomy as well as careful radiograph interpretations were essential in enhancing the root-cleaning procedure.